Meehania porphyrea, a new species from the treasured region of intricate geology in Gansu Province, China - Bai, Zengfu; Zhang, Zhihua; Dong, Zhongxiang; Tang, Jianquan; Zheng, Zhi; Yan, Xiaolu; Chen, Xuelin; Zhang, Ji (Phytotaxa, 2025)
Meehania porphyrea, a new species of Meehania, was discovered during extensive field surveys in the Xiaolongshan National Nature Reserve in Gansu, China. This region is located in the Qinba Mountains of southern Gansu, one of the province’s biodiversity hotspots, where the complex environment creates diverse habitats for a wide variety of plant species. Morphologically, M. porphyrea resembles Meehania fargesii (H. Lév.) C. Y. Wu, but the former is distinguished by its overall smaller plant size, often purple abaxial leaf surfaces, pale bluish purple flowers, smaller corolla, and narrow tubular calyx. Based on these distinct characteristics, we describe it here as a new species.